2022
DOI: 10.1159/000521912
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy Outcomes in Relapsed or Refractory Immune Thrombocytopenia according to First-Line Intravenous Immunoglobulin Response

Abstract: Introduction: Although splenectomy has long been second-line option for immune thrombocytopenia (ITP) patients, an indicator that reliably predicts the efficacy of splenectomy is still being explored. We investigated the treatment outcomes of splenectomy as a second-line therapy for relapsed/refractory ITP according to first-line intravenous immunoglobulin (IVIG) responses. Methods: Fifty-two adult patients treated with splenectomy as second-line therapy for ITP between 2009 and 2019 were included, and they we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
3
1
Order By: Relevance
“…More than 20 years ago, a Canadian study showed a strong positive association between response to IVIg and response to splenectomy 40 . This was confirmed in a recent study showing that with response to IVIg, the probability of response to splenectomy was extremely high, but in this study, the negative predictive value was not poor because 50% of the patients with failure of IVIg responded to splenectomy 41 . In our experience, we did not find a clear association between response to IVIg or splenectomy 42 .…”
Section: Are There Predictors Of the Response To Splenectomy?supporting
confidence: 70%
See 1 more Smart Citation
“…More than 20 years ago, a Canadian study showed a strong positive association between response to IVIg and response to splenectomy 40 . This was confirmed in a recent study showing that with response to IVIg, the probability of response to splenectomy was extremely high, but in this study, the negative predictive value was not poor because 50% of the patients with failure of IVIg responded to splenectomy 41 . In our experience, we did not find a clear association between response to IVIg or splenectomy 42 .…”
Section: Are There Predictors Of the Response To Splenectomy?supporting
confidence: 70%
“…40 This was confirmed in a recent study showing that with response to IVIg, the probability of response to splenectomy was extremely high, but in this study, the negative predictive value was not poor because 50% of the patients with failure of IVIg responded to splenectomy. 41 In our experience, we did not find a clear association between response to IVIg or splenectomy. 42 Therefore, splenectomy should not reasonably be contraindicated in a patient who does not respond to IVIg.…”
Section: Clinical Criteriacontrasting
confidence: 56%
“…Previous response to IVIg was associated with splenectomy response in three of seven case series 6 . In a recent monocentric study in Korea including 54 ITP patients splenectomized for ITP between 2009 and 2019, the response rate (≥30 × 10 9 /L and doubling of baseline value) after splenectomy was 50% in non‐responders to IVIg ( n = 10) and 95.2% in patients who previously achieved response with IVIg ( n = 42) 10 . Previous responses to corticosteroids, IVIg, TPO‐RAs, rituximab and dapsone were not associated individually with the achievement of sustained response after splenectomy in the recent study by Mageau et al 8 …”
Section: Splenectomymentioning
confidence: 92%
“…6 In a recent monocentric study in Korea including 54 ITP patients splenectomized for ITP between 2009 and 2019, the response rate (≥30 × 10 9 /L and doubling of baseline value) after splenectomy was 50% in non-responders to IVIg (n = 10) and 95.2% in patients who previously achieved response with IVIg (n = 42). 10 Previous responses to corticosteroids, IVIg, TPO-RAs, rituximab and dapsone were not associated individually with the achievement of sustained response after splenectomy in the recent study by Mageau et al 8 Having been treated with ≥2 drugs for ITP before splenectomy was associated with a lower rate of response (platelet count >50 × 10 9 /L at 1 month post-splenectomy) and with refractoriness (platelet count <30 × 10 9 /L at last follow-up) in the study by Vianelli et al in both univariable and multivariable models. 7 Previous treatment with ≥4 drugs was associated with a decreased probability of sustained response after splenectomy in the French multicentre study conducted between 2011 and 2020, with 79.8% of patients exposed to ≥2 drugs for ITP before splenectomy.…”
Section: Previous Treatmentsmentioning
confidence: 99%
“…
Dear Editor, Kwag et al [1] describe splenectomy outcomes in 45 patients with relapsed or refractory immune thrombocytopenia (ITP) according to first-line response to intravenous immunoglobulins (IVIG). Both stable responders and poor responders to IVIG had high initial responses to splenectomy.
…”
mentioning
confidence: 99%